2018
DOI: 10.1016/j.geoforum.2018.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Professionals with borders: The relationship between mobility and transnationalism in global firms

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 56 publications
0
14
0
1
Order By: Relevance
“…This work points to the importance of global internal policies, systems and structures as well as informal procedures in connection with local subsidiary autonomy (2016a), while revealing differences in the way transfer between regions and localities were led and controlled (2016b). Focusing on the transnational mobility of professionals, Spence et al (2018) outlined geographical, temporal and functional mobility constraints. Through a cross-national study of global accounting firms, they found that the transnational aspect shapes local practices through knowledge-sharing activities.…”
Section: Transnational Knowledge-intensive Service Provisionmentioning
confidence: 99%
“…This work points to the importance of global internal policies, systems and structures as well as informal procedures in connection with local subsidiary autonomy (2016a), while revealing differences in the way transfer between regions and localities were led and controlled (2016b). Focusing on the transnational mobility of professionals, Spence et al (2018) outlined geographical, temporal and functional mobility constraints. Through a cross-national study of global accounting firms, they found that the transnational aspect shapes local practices through knowledge-sharing activities.…”
Section: Transnational Knowledge-intensive Service Provisionmentioning
confidence: 99%
“…In particular, small and medium-sized Italian companies, which make up the majority of the Italian economy (Corbetta, 1995;Del Giudice et al, 2017;Russo & Tencati, 2009) are aware that the survival of the company is linked to the training and growth of its employees. This purpose is achieved through a fair remuneration (Riley, Michael, & Mahoney, 2017) and this is only possible with active collaboration with professionals (Spence, Sturdy, & Carter, 2018) and institutions in order to tackle economic evolution and the possible internationalization (Dimitratos, Voudouris, Plakoyiannaki, & Nakos, 2012). The future perspective will be the analysis of a dashboard of common indicators that allow a uniform detection of all the needs and a greater response to the demand and to the market changes in real time.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…We suggest that transnationally, professionalism is often linked more tightly to issues than to formal boundaries of professional groups (Seabrooke and Henriksen 2017). Recently scholars have noted how professionals have become more transnational and partially delinked from national professional associations (Seabrooke 2014;Carter et al 2015;Harrington 2016;Brock 2016), while also maintaining selective ties to local networks (Dezalay and Garth 2016;Block et al 2018;Spence et al 2018).…”
Section: Issue Professionalsmentioning
confidence: 99%